Nursing care in threatened preterm labor in the obstetrics and gynecology department of a national hospital - Bueno Huamán, Ruth Noemí; Villanueva Sánchez, Carmen Del Pilar; Vivanco Hilario , Sofia Dora (AG Salud, 2023)
The threat of preterm birth is a pathology that puts the life of the mother and baby at risk; it occurs one in every 10 births and is a serious public health problem. The objective was to manage the nursing care process for a pregnant woman with a threat of preterm birth. The study had a qualitative approach, a single case type of study applying the method of the nursing care process in its 5 stages, the study subject was a 35-year-old patient with a diagnosis of threatened preterm birth. In the assessment stage, the guide of Maryori Gordon’s 11 functional patterns was applied, allowing problems and needs to be identified through the interview and data from the clinical history. Identifying 10 nursing diagnoses based on NANDA-I taxonomy II, prioritized: labor pain, risk of alteration of the maternal/fetal dyad and CP infection; In the planning, the care plan prepared with the NOC and NIC classification was applied, in the execution stage nursing care was provided related to the control of alarm signs, reduction of labor pain and maternal-fetal complications, application of therapeutic measures, were assessed by differentiating the baseline score with the achievement score, resulting in an updated care plan with a change score of -2, 0 and +1. In conclusion, the nursing care process was managed, providing quality and humanized care to the patient.